Orthostatic Ex-Vivo Lung Perfusion (EVLP): A Proof of Concept - Massimo Boffini; Andrea Costamagna; Matteo Marro; Erika Simonato; Paola Cassoni; Luca Bertero; Vito Fanelli; Cristina Barbero; Luca Brazzi; Mauro Rinaldi (Transplant International, 2024)
The key goal in lung donation remains the improvement of graft preservation with the ultimate objective of increasing the number and quality of lung transplants (LTx). Therefore, in recent years the field of graft preservation focused on improving outcomes related to solid organ regeneration and restoration. In this contest Ex-Vivo Lung Perfusion (EVLP) plays a crucial role with the purpose to increase the donor pool availability transforming marginal and/or declined donor lungs suitable for transplantation. Aim of this proof of concept is to test the safety, suitability and feasibility of a new tilting dome for EVLP designed considering the dorsal lung areas as the “Achilles’ heel” of the EVLP due to a more fluid accumulation than in the supine standard position.